1978
DOI: 10.1111/j.1600-0714.1978.tb01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and immunological aspects of tooth transplantation

Abstract: Histopathological studies of teeth transplanted between genetically identical animals and to animals in which the immune response is suppressed or enhanced show that autografts and isografts degenerate but then are repaired, whereas allografts show a bewildering array of changes from almost total destruction to total repair. Some explanations for the repair of teeth in an immunologically hostile environment are put forward.The immunological aspects of tooth transplantation are also reviewed. Transplanted teeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
2
6
0
Order By: Relevance
“…In previous studies on allotransplantation of monkey teeth, only small areas of normal periodontal ligament healing has been described in other areas of the root (10, 11), even in closely MHC‐class I and class II matched rhesus monkeys (12). This seems to be in accordance with allotransplantation studies in inbred strains of rodents, where only the closest MHC and no‐MHC matches seem to heal equally with iso‐ and autograft (8, 9, 35). The interesting finding in the present study, that normal PDL healing of an allograft was found in localized areas where the root surface was in near anatomical proximity to an adjacent untreated root surface (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In previous studies on allotransplantation of monkey teeth, only small areas of normal periodontal ligament healing has been described in other areas of the root (10, 11), even in closely MHC‐class I and class II matched rhesus monkeys (12). This seems to be in accordance with allotransplantation studies in inbred strains of rodents, where only the closest MHC and no‐MHC matches seem to heal equally with iso‐ and autograft (8, 9, 35). The interesting finding in the present study, that normal PDL healing of an allograft was found in localized areas where the root surface was in near anatomical proximity to an adjacent untreated root surface (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…In rodents, where most studies on the basic immunobiology of tooth allografting has been carried out, root resorption has been ignored or only sporadically mentioned in the evaluation of tooth graft rejection (8, 9). This in combination with anatomical and biological differences between rodent and human dental structures, as well as the often used heterotopic experimental design, makes the extrapolation of experimental results in this model to the clinical situation in humans difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies on allografts of monkey teeth, only small areas of normal PDL healing have been described (Fong et al, 1968;Shulman and Kalis, 1970), even in close MHC-class I and class II-matched rhesus monkeys (Riviere, 1981). This seems to be in accordance with allograft studies in inbred rodent strains, where only the closest MHC and non-MHC matches seem to heal equally with isografts and autografts (Atkinson, 1978). These previous studies suggested that immune rejection reaction might not be the only cause of failure in normal PDL healing.…”
Section: Discussionsupporting
confidence: 89%
“…In rodents, many studies on the basic immunobiology of the tooth allograft have been performed (Atkinson, 1978). Especially in mouse, teeth size is too small to be handled rightly during transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In previous experimental studies, the histology of tooth allograft rejection, leading to root resorption and ankylosis of the allograft, has been studied (1,8,9,(27)(28)(29)(30). Resorption was predominantly located in the intra-alveolar part of the periodontal ligament (8,9).…”
Section: Discussienmentioning
confidence: 99%